CHARACTERISTIC OF SPAWNERS FOR AMUR STURGEON ACIPENSER SCHRENCKII FROM WARM-WATER CAGE FARM IN THE PROCESS OF LONG-TERM EXPLOITATION - E. I. Rachek; D. Y. Amvrosov (Известия ТИНРО, 2018)
Cultivation, biological and production parameters of domesticated spawners of amur sturgeon in the age from 8 to 24 years are described for the warm-water cage farm conditions. In three year-classes bred from native spawners in the cages, the females mature firstly in the age 8–10 years, while males in the age 6–7 years. The females have larger body weight, length, girth, and fatness than males in all age groups from 8 to 24 years. The males are able to produce 40–350 mL of high-quality sperm per one drain-off session, while the firstmatured females produce 0.7–2.3 kg of eggs. Majority of the females (75 %) spawn annually or biennially. Average fecundity of the females in age 8–24 years is 200,000 eggs (3.82 kg, 7,500 eggs/kg), their average oosomatic index before spawning is 14.5. The females with the highest fecundity have the age 17–23 years and produce up to 520,000 eggs (7.0–10.5 kg, up to 13,500 eggs/kg), the highest oosomatic index is 24.5 %. In total, the females which reach the age 21–24 years produced on average 22–31 kg of roe in 6–8 spawnings that is equal to 90–98 % of their body weight, and the most productive ones (27 % of total number) produced 29–43 kg of roe, or 103–138 % of their body weight. The females are technologically welladaptable for maintenance. Their survival in the period of exploitation is 65 %.